One Hour-Post-load Plasma Glucose ≥155 mg/dl in Healthy Glucose Normotolerant Subjects Is Associated With Subcortical Brain MRI Alterations and Impaired Cognition: A Pilot Study - Perticone, Maria; Di Lorenzo, Cherubino; Arabia, Gennarina; Arturi, Franco; Caroleo, Benedetto; Tassone, Bruno; Pujia, Roberta; Fiorentino, Teresa Vanessa; Chiriaco, Carmelina; Sesti, Giorgio; Quattrone, Aldo; Perticone, Francesco (Frontiers in Aging Neuroscience, 2021)
Background: Glucose alterations are associated with impaired cognition. 1-h-postload plasma glucose>155 mg/dL in non-diabetics confers an increased risk of cardiovascular events and diabetes. The aim of this pilot study was to investigate whether 1-h-postload plasma glucose >155 mg/dL negatively affects brain subcortical regions and cognitive function. Methods: We enrolled 32 non-diabetic subjects. Patients were divided into two groups on the basis of 1-h postload plasma glucose value of 155 mg/dL: NGT 1-h-high and NGT 1-h-low. All subjects underwent 3-Tesla MRI and administration of standard neuropsychological tests. Results: NGT 1-h-high subjects showed significantly lower values of both right (4.9±0.9 vs 5.1±0.9 ml) and left (4.8±1.1 vs 5.1±1.1 ml) hippocampal hemisphere volume, while right hemisphere hippocampal diffusivity was lower in the NGT 1-h-high group (10.0±0.6 vs 10.6±0.5 10-4mm2s-1). NGT 1-hour-high subjects also showed poorer memory performances. In particular, for both RAVLT immediate-recall and FCSRT delayed total recall, we found lower cognitive test scores in the NGT-1h-high group (26.5±6.3 and 10.4±0.3, respectively). Conclusions: 1-h-postload hyperglycaemia is associated with morpho-functional subcortical brain alterations and poor memory performance tests.